PENGARUH ZAKAT DAN PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA KPP PRATAMA JAMBI PELAYANGAN) - Nurasiah Delka; Usdeldi; Aztyara Ismadharliani (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine and identify the effect of zakat and services on taxpayer compliance. The population in this study were all taxpayers registered at KPP Pratama Jambi Servant. The sampling technique in this study used a sampling technique, namely individual taxpayers who had reported their SPT at KPP Pratama Jambi Servant. Data collection techniques in this study used questionnaires which were distributed directly to the respondents. The questionnaires collected in this study amounted to 100 questionnaires. The method of data analysis in this study used quality tests, classic assumption tests and hypothesis testing and the tools used were multiple linear regression analysis with the help of SPSS tools. This study obtained the results that zakat has no effect on taxpayer compliance. While Services are influenced by Taxpayer Compliance. Based on the results of multiple linear regression tests from the T test, it can be concluded that tax services have an influence on taxpayer compliance with a t count of 6.175 > t table of 1.983 and a Sig value of 0.000 <0.05. While Zakat has no partial effect on Taxpayer Compliance with a t count value of 0.703 <t table 1.983 and a Sig value of 0.484 > 0.05. And based on the results of the F Test, it can be concluded that Zakat and Services simultaneously affect Taxpayer Compliance.